Seasonal variations in the light-absorbing properties of water-soluble and insoluble organic aerosols in Seoul, Korea - Kim, Hwajin; Kim, Jin Young; Jin, Hyoun Cher; Lee, Ji Yi; Lee, Se Pyo (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The spectral properties of light-absorbing organic aerosol extractions were investigated using 24-h average fine particulate matter (PM2.5) measurements from October 2012 to September 2013 in Seoul, Korea. The light-absorption spectra of water and methanol extracts exhibited strong evidence of brown carbon with Absorption Angstrom Exponent (AAE; fitted between 300 and 700 nm) ranges of 5.84-9.17 and 4.08-5.75, with averages of 7.23 +/- 1.58 and 5.05 +/- 0.67, respectively. The light absorption of both extracts at 365 nm (Abs(365)), which is typically used as a proxy for brown carbon (BrC), displayed strong seasonal variations and was well correlated with both water-soluble organic carbon (WSOC; r = 0.81) and organic carbon (OC; r = 0.85), indicating that both primary and secondary organics were sources of BrC in this region. Normalizing the Abs(365) of water and methanol extracts to the mass of WSOC and OC yielded average solution mass absorption efficiency (MAE(365)) of 0.28-1.18 and 0.44-1.45 m(2) g(-1) C, respectively. MAE(365) in Korea were in the same range or slightly lower than those in China, however, despite the same ranges, the seasonal variations were different, suggesting that the sources of light absorbers could be different. Combining the AAE, Abs(365), and MAE(365) of both extracts and a detailed chemical speciation of filter extracts identified the compounds responsible for the temporal variations of BrC in Korea. During summer, secondary organic aerosol (SOA), photochemically generated from anthropogenic emissions, was the major source; however, during winter, long range transported organics or transported BrC seem to be a source of BrC in Korea, a downwind site of China, where severe smog and BrC were observed during this season. Biomass burning was also an important source; however, unlike in previous studies, where it was identified as a major source during winter, here, it contributed during the whole year. Although many of its properties, sources, and potential impacts remain unknown, this is the first result showing that BrC was prevalent in the PM2.5 fraction in Seoul throughout the year. Also this suggest that BrC and its sources can be long range transported, emphasizing that the optical effect of BrC might be important in East Asia. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ABSORPTION ANGSTROM EXPONENT; BROWN CARBON ABSORPTION; OPTICAL-PROPERTIES; ELEMENTAL CARBON; BLACK CARBON; PARTICLES; EXTRACTS; IMPACT; MATTER; CHINA